Effectiveness of Soursop Leaf Extract (Annona muricata) and Ylang-ylang Flowers (Cananga odorata) as a Larvasicide to Remove Mosquito Flars - Sarah Annisa Alifvina; Aminah Asngad (Program Studi Pendidikan Biologi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kuningan, 2025)
One of the few countries with high humidity levels, it can cause poor air quality and an increase in diseases such as dengue fever. Dengue fever is a disease caused by the Aedes aegypti mosquito. Due to the large number of cases of dengue fever, various types of drugs have emerged to treat this condition. Predator, genetics, pathogen and parasite control, as well as physical, biological and chemical control are several ways to control larvae. Efforts to control mosquitoes can be made by using mosquito repellent repellents by using plants that come from nature which contain essential oils as environmentally friendly repellents. One of the plants that contain essential oils is soursop leaves and ylang-ylang flowers. The aim of this research was to determine the effectiveness of soursop leaves and ylang-ylang flowers as larvicides to eradicate mosquito larvae. This research is experimental in nature with the samples used, namely Culex type mosquito larvae. This research was conducted at the Biology Laboratory, Faculty of Teacher Training and Education, Universitas Muhammadiyah Surakarta. The samples for this study were 28 containers with an initial number of larvae of 25 individuals. The results showed that there were several mosquito larvae that experienced death with the lowest mortality in F1D1 with an average of 20 deaths and the highest mortality in F3D3 with an average of 23.67 deaths. Mosquito larvae experienced death with the highest time at 9 hours of observation and the time of death decreased at 12 hours of observation. The use of larvicidal extracts from soursop leaves and ylang ylang flowers is more effective in reducing the number of mosquito larvae with F3 having the highest average number of deaths with a dose of 2.5 g of soursop leaves: 7.5 ylang ylang flowers within 9 hours.